TRANSPHENOIDAL SURGERY OF SELLAR PATHOLOGY - RETROSPECTIVE ANALYSIS OF 180 PATIENTS SUBMITTED TO SURGERY - Cerejeira, Rui (2006)
Surgical access to sellar region can be obtained with transcranial (high) and extracranial (low) approaches.Sublabial-transphenoidal and endonasal-transphenoidal (or trans·septo-sphenoidal) are the most common used approaches.Other approaches like transantral transphenoidal (using o Coldwell-Luc operation) and transethmoidal (via on external ethmoidectomy) are less frequently used.Endonasal-transphenoidal approach was the procedure of choice in patients submitted to surgery at Coimbra University Hospital (HUC) by Neurosurgery and ENT teams.The authors analyse the Rhino-Neuro-Surgery team' s experience of HUC between January, 2000 and December, 2005 in what concerns to tronsphenoidal approach to sellar pathology.